A protocol for differential staining of cartilages and ossified bones in fetal and adult mouse skeletons using alcian blue and alizarin red S. (1st October 2020) - Liao, Yu-Jing; Tang, Pin-Chi; Chen, Lih-Ren; Yang, Jenn-Rong
ABSTRACT: The technique for clearing and staining whole specimens consists of many steps. This study discusses the alcian blue/alizarin red S staining method and aims to provide a useful reference and review for users who intend to do this staining. To specifically address the influences of tissue removal on staining results, the mouse fetuses at embryonic stage E18.5 and adult mice at 12 weeks of age were used in this study. The fetuses were divided into three groups: Group 1 skin, muscle, and viscera removed, Group 2 skin and muscle removed, and Group 3 viscera removed. For successful skeletal staining, it was concluded that (1) skin removal from fetuses was necessary for alcian blue staining but unnecessary for alizarin red S staining, (2) removal of muscle surrounding thorax and neck of fetuses could improve transparency effects, (3) retaining fetal viscera would not significantly affect transparency but might avoid the tissue damage, and (4) complete skin, muscle, and viscera removal were essential for good staining of adult mice. The representative images and detailed staining procedures might be good for researchers presently using alcian blue and alizarin red S staining to differentiate cartilages and ossified bones.